Marked Succession of Cyanobacterial Communities Following Glacier Retreat in the High Arctic - Pessi, Igor S; Pushkareva, Ekaterina; Lara, Yannick; Borderie, Fabien; Wilmotte, Annick; Elster, Josef (Microbial ecology, 2019)
Cyanobacteria are important colonizers of recently deglaciated proglacial soil but an in-depth investigation of cyanobacterial succession following glacier retreat has not yet been carried out. Here, we report on the successional trajectories of cyanobacterial communities in biological soil crusts (BSCs) along a 100-year deglaciation gradient in three glacier forefields in central Svalbard, High Arctic. Distance from the glacier terminus was used as a proxy for soil age (years since deglaciation), and cyanobacterial abundance and community composition were evaluated by epifluorescence microscopy and pyrosequencing of partial 16S rRNA gene sequences, respectively. Succession was characterized by a decrease in phylotype richness and a marked shift in community structure, resulting in a clear separation between early (10-20 years since deglaciation), mid (30-50 years), and late (80-100 years) communities. Changes in cyanobacterial community structure were mainly connected with soil age and associated shifts in soil chemical composition (mainly moisture, SOC, SMN, K, and Na concentrations). Phylotypes associated with early communities were related either to potentially novel lineages (< 97.5% similar to sequences currently available in GenBank) or lineages predominantly restricted to polar and alpine biotopes, suggesting that the initial colonization of proglacial soil is accomplished by cyanobacteria transported from nearby glacial environments. Late communities, on the other hand, included more widely distributed genotypes, which appear to establish only after the microenvironment has been modified by the pioneering taxa.
Keywords: genotyp; půdní mikrobiologie; High-Throughput Nucleotide Sequencing; Glacier forefield; RNA, Ribosomal, 16S; Arctic Regions; Phylogeny; půda; DNA, Bacterial; Svalbard; High Arctic; Biodiversity; sinice; RNA ribozomální 16S; Soil Microbiology; biodiverzita; Proglacial soil; vysoce účinné nukleotidové sekvenování; ledový příkrov; Genotype; Soil; Primary succession; DNA bakterií; Arktida; High-throughput sequencing; Ice Cover; fylogeneze; Cyanobacteria